It's Not Your Fault! Strategies for Solving Toilet Training and Bedwetting Problems - Barone, Joseph (Rutgers University Press, 2015)
Millions of children over the age of five wet their beds every night. Many parents think they must be doing something wrong when their five-year-old is still in diapers while their friends’ children are perfectly trained by eighteen months of age. This undoubtedly is a very embarrassing and frustrating problem for both the parent and child, and can interfere with family dynamics and a child’s ability to enjoy ordinary social situations. It’s Not Your Fault! offers evidence-based strategies for parents who need assistance with toilet training and helping their child with urinary control issues. Dr. Joseph Barone, M.D., provides proven techniques that bring bedwetting to a happy conclusion. Frequently, parents are misguided by bad advice from friends, TV talk shows, the Internet, or parenting books. With many years of clinical experience, Dr. Barone shares valuable, practical information for parents to guide them through the basics of toilet training and bedwetting, and presents management plans to resolve any difficulties that occur. A comprehensive guide, this book covers everything parents need to know about normal toilet training and bedwetting, as well as step-by-step solutions based on testing and research in a real-world setting to help children suffering from delayed toilet training, bed wetting, and daytime urinary wetting. It’s Not Your Fault! provides hope and guidance to those desperate to help their children overcome urinary control and toilet training problems. Dr. Barone sets parents on a course that makes things better for both themselves and their children